Economic Growth of Nepal and Its Neighboring Countries - Bajracharya, Sovit Lal (Economic Journal of Development Issues, 2016)
Economic growth and poverty are interrelated. Generally, economic development is believed to reduce poverty. In Nepal, over the last fifteen years, poverty has remarkably come down in spite of lower economic growth meaning that reducing poverty would be much easier if economic growth rate could be increased. Higher economic growth can never be attained unless production and productivity rise. Regarding economic growth of South Asian Countries, Afghanistan accorded first place followed by 10.2 percent, Bhutan second 9.7 percent, China third 7.8 percent. Nepal Sixth 4.6 percent and Maldives occupies last followed by 3.5 percent for the year 2012.Economic Journal of Development Issues Vol. 17 & 18 No. 1-2 (2014) Combined Issue, Page: 163-174